2015
DOI: 10.1002/rcm.7242
|View full text |Cite
|
Sign up to set email alerts
|

Derivatization of bisphenol A and its analogues with pyridine‐3‐sulfonyl chloride: multivariate optimization and fragmentation patterns by liquid chromatography/Orbitrap mass spectrometry

Abstract: RationaleDue to the growing restrictions on the use of bisphenol A (BPA), several other bisphenols are gaining importance as substitutes for BPA in a variety of applications. There is, therefore, a real need for selective and sensitive methods based on mass spectrometry which will allow the human exposure to these new bisphenols to be assessed.MethodsDerivatization of BPA and its substitutes with pyridine‐3‐sulfonyl chloride is used to enhance the detection capability of bisphenols by electrospray ionization m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(23 citation statements)
references
References 37 publications
0
22
1
Order By: Relevance
“…Furthermore, by increasing the molecular mass of the analytes, the signal-to-noise ratio is also increased. Both features result in a higher sensitivity 26 . To our knowledge, derivatization has rarely been applied in the field of dental research 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, by increasing the molecular mass of the analytes, the signal-to-noise ratio is also increased. Both features result in a higher sensitivity 26 . To our knowledge, derivatization has rarely been applied in the field of dental research 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Despite being classified as a reprotoxic and banned for use in children's bottles and cups in Canada, the European Union, as well as in more than ten states in the United States of America, BPA is still widely used . The monomer BPA is a chemical precursor in the production of many vinyl ester resins, unsaturated polyester resins and cyanate esters . BPA also serves as a basis for 85% of the world's production of epoxy resins, which are industrially common prepolymers that contain oxirane groups (Figure ) .…”
Section: Introductionmentioning
confidence: 99%
“…It showed that CCR has the best ionization efficiency in the ESI source. The structure of LRBC, a commercial sulforhodamine derivatization agent, was unstable; it easily transformed to its lactone form affected by the solvent environment . This caused the LRBC molecule to lose a positive charge (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The structure of LRBC, a commercial sulforhodamine derivatization agent, was unstable; it easily transformed to its lactone form affected by the solvent environment. [26,51] This caused the LRBC molecule to lose a positive charge ( Fig. 2(C), (2)), which was not conducive to the MS detection sensitivity of its derivatives.…”
Section: Optimization Of Derivatization Conditionsmentioning
confidence: 99%